2015
DOI: 10.1371/journal.pone.0131555
|View full text |Cite
|
Sign up to set email alerts
|

Major Sources of Organic Matter in a Complex Coral Reef Lagoon: Identification from Isotopic Signatures (δ13C and δ15N)

Abstract: A wide investigation was conducted into the main organic matter (OM) sources supporting coral reef trophic networks in the lagoon of New Caledonia. Sampling included different reef locations (fringing, intermediate and barrier reef), different associated ecosystems (mangroves and seagrass beds) and rivers. In total, 30 taxa of macrophytes, plus pools of particulate and sedimentary OM (POM and SOM) were sampled. Isotopic signatures (C and N) of each OM sources was characterized and the composition of OM pools a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 58 publications
(95 reference statements)
3
58
0
2
Order By: Relevance
“…The mean δ 15 N value of the POM was +7.04 ± 3.81‰ (Figure and Table ). On the basis of published isotopic values from various sources, the mean value suggests that the nitrogen was derived from terrestrial sewage (+3 to +8‰) [ Higueras et al ., ; Khodse and Bhosle , ; Lamb et al ., ; Rogers , ], marine upwelling (+4 to +7‰) [ Bode , ; Briand et al ., ; Lamb et al ., ] and animal waste (>10‰) [ Lindau et al ., ; Sánchez et al ., ; Swart et al ., ]. Atmospheric dinitrogen is 0‰ [ Mariotti , ], terrestrial plant (vascular plant) nitrogen has a δ 15 N value of −2 to +2‰ [ Higueras et al ., ; Kendall et al ., ; Lin et al ., ], and nitrogen fixation and assimilation have δ 15 N values of 0 to +1‰ [ Kaiser et al ., ; Lamb‐Wozniak , ] and +1 to +3‰ [ Burford et al, ; Higueras et al ., ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean δ 15 N value of the POM was +7.04 ± 3.81‰ (Figure and Table ). On the basis of published isotopic values from various sources, the mean value suggests that the nitrogen was derived from terrestrial sewage (+3 to +8‰) [ Higueras et al ., ; Khodse and Bhosle , ; Lamb et al ., ; Rogers , ], marine upwelling (+4 to +7‰) [ Bode , ; Briand et al ., ; Lamb et al ., ] and animal waste (>10‰) [ Lindau et al ., ; Sánchez et al ., ; Swart et al ., ]. Atmospheric dinitrogen is 0‰ [ Mariotti , ], terrestrial plant (vascular plant) nitrogen has a δ 15 N value of −2 to +2‰ [ Higueras et al ., ; Kendall et al ., ; Lin et al ., ], and nitrogen fixation and assimilation have δ 15 N values of 0 to +1‰ [ Kaiser et al ., ; Lamb‐Wozniak , ] and +1 to +3‰ [ Burford et al, ; Higueras et al ., ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, pollution from more extensive region and anthropogenic activities from riverine sewage discharges adjacent to reefs should be focused to effectively reduce human-derived nutrients on reefs.Numerous studies have shown that natural stable isotopes (d 13 C and d 15 N) of particulate organic matter (POM) are good nutrient source indicators, as phytoplankton and other microorganisms present in the water column take up and turn over nutrients in a relatively short period of time (hours to weeks) [Loh and Bauer, 2000]. Stable isotopes of POM can be used to investigate the origin, fate, and seasonal variation in nutrients in aquatic environments [Briand et al, 2015;Cao et al, 2015]. Marine POM comprises a spectrum of colloidal and particulate matter from terrestrial detritus, riverine particulate matter, marine tidally Key Points:Isotopic values revealed strong anthropogenic influences on coral reefs Hydrodynamic conditions coupled with human activities have profound implications for nutrient concentrations There might be more inputs from terrestrial detritus and anthropogenic-derived discharges in dry seasons…”
mentioning
confidence: 99%
“…In the KKB marine system, terrestrial inputs to SOM generated marked depletions in SOM δ 13 C values ( M ± SD : –24.5 ± 0.6‰) compared to other Pacific bays without aquaculture, including those in Southwest Thailand (–21.0 ± 2.0‰; Kuramoto & Minagawa, ), Korea (–20.6 ± 0.9‰; Kang et al, ) and New Caledonia (–17.9 ± 3.6‰; Briand et al, ). These more enriched δ 13 C SOM values indicate greater contributions to marine SOM from marine benthic primary producers (seagrass, algal turf, macroalgae).…”
Section: Discussionmentioning
confidence: 99%
“…A 13 C‐enrichment in mangrove sediments relative to mangrove plant materials is either from the mangrove signature being diluted through mixing with material enriched in 13 C or there is a substantial change in isotopic composition associated with OM degradation during early diagenesis (Muzuka & Shunula, ). The first case can occur due to the presence of (epiphytic) algae in mangrove SOM, as a compilation of ẟ 13 C values for mangrove benthic algae, including epiphytic and edaphic algae, shows that algae are generally enriched relative to mangroves leaves (Bouillon et al, ; Briand et al, ). Bacteria and fungi cause the second scenario: decomposition of mangrove leaves, seagrasses and other plant materials enrich 13 C by up to 2‰ (Fourqurean & Schrlau, ; Lehman, Bernasconi, Barbieri, & McKenzie, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation